The processes of hospital discharge and recovery after blunt thoracic injuries: The patient's perspective - Edward Baker; Andreas Xyrichis; Christine Norton; Philip Hopkins; Geraldine Lee (Wiley, 2022)
Abstract Aims The aim of this study was to explore hospital discharge processes and the self‐management of recovery in the early post‐discharge period after blunt thoracic injury from a patient perspective. Design Qualitative interview study. Methods Interviews were conducted with participants recruited from 8 sites across England and Wales between November 2019-May 2020. Semi‐structured interviews were conducted between 5-8 weeks after hospital discharge, and in total, 14 interviews were undertaken. These interviews were recorded, transcribed and analysed using thematic coding. Results Three main themes were identified from the analysis: (a) challenges in the discharge process, (b) coping at home after discharge and (c) managing medications at home. Pain was a dominant thread running throughout all themes which represented an important quality and safety concern for all participants. Associated concerns included insufficient preparation and education for hospital discharge, ineffective communication and subsequent unsafe use of opioids at home highlighting unmet patient care needs.